In Armageddon's shadow : the Civil War and Canada's Maritime Provinces - Marquis, Greg (Gorsebrook Research Institute for Atlantic Canada Studies, Saint Mary's University, 1998)
"The United States had important and long-standing economic, social, and kinship ties with Nova Scotia, New Brunswick, and Prince Edward Island that were profoundly shaken by the Civil War. In this account, Greg Marquis explores the shadow cast on the Maritimes and its people by America's bloodiest conflict." "In Armageddon's Shadow chronicles events as they unfolded and highlights the very real threat of conflict between Britain and the United States. Major crises such as the highjacking of the Chesapeake by Confederate partisans and the destructive cruise of the CSS Tallahassee - the only Confederate warship to reach a mainland British North American port - in addition to Halifax's growing importance as a communications link for the South and the Maritimes' involvement in blockade running are recounted in detail."--Jacket